Application of STAD-Type Cooperative Model in Improving Student Learning Outcomes in Mathematics Learning in Class V SDN I East Suwawa Regency Bone Bolango - Hendra Saputra S. Adiko; Jumirta Diuli (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The objective of this research to improve student's learning outcomes on the material of presenting mathematics learning data through a cooperative model type stad in class V SDN 1 Suwawa Timur. The method used action class research that implemented in 2 cycles. Data collection techniques in this study were in the form of observation of teacher activities, observation of student activities, tests, and documentation. Initial observations of student learning outcomes on average were students in the data presentation material from 28 students, there were 7 students who completed (27%) and 21 students did not complete or 75%. In the implementation of the first cycle of class action only 15 students (54%). In the second cycle increased to 25 people (89%). From the results of the research and discussion carried out, the research on the application of the Stad Type Cooperative Model in Improving Student Learning Outcomes in Mathematics Learning in Class V of SDN I Suwawa Timur, Bone Bolango Regency increased.